THE INFLUENCE OF SOFT SKILLS AND HARD SKILLS ON WORK READINESS WITH SELF-EFFICACY AS AN INTERVENING VARIABLE AMONG MANAGEMENT STUDENTS 2021 - Yusril Ramadhan Sembiring; Yanita; Nur Faliza; Nurmala (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study is to analyze the influence of soft skills and hard skills on the work readiness of Management Study Program students at Malikussaleh University class of 2021, considering the role of self-efficacy as an intervening variable. The research method used is a quantitative approach with a survey, where data is collected through questionnaires and analyzed using SEM PLS analysis with the help of Smart PLS application and mediation tests. The analysis results reveal that soft skills, hard skills, and self-efficacy significantly contribute to improving students' work readiness, both directly and through the mediating role of self-efficacy, which has proven to be a partial mediator. These findings indicate that strengthening soft skills and hard skills, along with enhancing self-efficacy, is an essential strategy to prepare graduates to face challenges in the professional world.